REHABILITASI LAHAN KRITIS SEBAGAI PRAKTIK DISASTER GOVERNANCE BERBASIS KOMUNITAS DI KAWASAN DIENG PLATEAU KABUPATEN WONOSOBO - Siti Mutmainah; Priyatno Harsasto; Laila Alfirdaus; kushandajani - (Journal of Politic and Government Studies, 2018)
ABSTRACTDieng Plateau Area is a protected area which means that the conservation of nature in it must be maintained to ensure sustainable livelihood (sustainable livelihood). The biggest challenge in Dieng's recovery effort is the rehabilitation of critical land in community-owned land areas. This research uses descriptive qualitative approach method with case study located in Dieng Plateau area of Wonosobo Regency covering 6 Villages in Kejajar Subdistrict, Dieng, Sembungan, Buntu, Kreo, Patak Banteng, and Sigedang Village and one Village in Garung Subdistrict, Mlandi Village . Technique of data collection is done by observation, interview, and documentation.The results showed that critical land rehabilitation activities were carried out with the cooperation between communities and the government through the support of various related stakeholders including private parties, NGOs and other NGOs. Approaches are made through sustainable farming systems by farmers' Union through agroforestry, conservation plants (coffee, carica, eggplant, etc.), and intercropping with other commodities other than potatoes. While Bhineka Karya through off farm approach, that is tourism (agro tourism, nature tourism, history and culture) and geopark also become the most logical approach that strived. Both approaches are based on different biogeophysical potentials and conditions among the research sites so that critical land rehabilitation activities can be successful. The economic orientation of the community becomes the determinant of the sustainability of the programs of both approaches, to the extent that tourism activities are still inferior to agricultural activities. In addition, the socio-economic conditions of the community, such as low education and the increasingly narrow land ownership ratio, are also a hindrance to the success of critical land rehabilitation with off farm approach, so that sustainable agriculture approach is superior to off farm approach.Strengthening social capital in critical land rehabilitation activities through studies in three typologies of social capital (Bonding social capital, Bridging social capital and Linking social capital) viewed from social, economic, and cultural aspects of society shows that cooperation between communities and government through the support of the related stakeholders have increased the capacity of the community in controlling the problems of increasingly severe land degradation. So the role of the community, especially Bhineka Karya and Serikat Petani in critical land rehabilitation activities has reflected the community-based disaster governance practice in disaster management in Dieng Plateau district of Wonosobo regency.Keywords: Community Based Disaster Governance, Critical Land Rehabilitation, Dieng Plateau Area Wonosobo.